Gestión integral de la biodiversidad en el Distrito Capital. Aportes para una gobernanza urbana (2016)
Based on the recognition of the geographical context and environmental institutions of Bogotá, this paper attempts to propose some insights for the comprehensive management of urban-region biodiversity, taking into account the contribution of the social and institutional history of the city. Considering this, it could support the promotion of common practices and languages in order to develop persistent processes of social appropriation of biodiversity which could become part of a broader urban policy. The document propose some principles and actions, based on the different ways of seeing and use the biodiversity in Bogotá, which it can be assumed as a public good that maintains and improves the quality of life in the city and its region.